Instrumentation and control systems - Bolton, W. (William), 1933- (Newnes, 2021)
Instrumentation and Control Systems, Third Edition, addresses the basic principles of modern instrumentation and control systems, including examples of the latest devices, techniques and applications. The book provides a comprehensive introduction on the subject, with Laplace presented in a simple and easily accessible form and complemented by an outline of the mathematics that would be required to progress to more advanced levels of study. Taking a highly practical approach, the author combines underpinning theory with numerous case studies and applications throughout, thus enabling the reader to directly apply the content to real-world engineering contexts. Coverage includes smart instrumentation, DAQ, crucial health and safety considerations, and practical issues such as noise reduction, maintenance and testing. PLCs and ladder programming is incorporated in the text, as well as new information introducing various software programs used for simulation. The overall approach of this book makes it an ideal text for all introductory level undergraduate courses in control engineering and instrumentation.